Ozanimod-mediated remission in experimental autoimmune encephalomyelitis is associated with enhanced activity of CNS CD27low/- NK cell subset - Kamyan, Doua; Hassane, Maya; Alnaqbi, Alanood; Souid, Abdul-Kader; Rasbi, Zakeya Al; Tahrawi, Abeer Al; Shamsi, Mariam Al (Frontiers in Immunology, 2024)
Background: Ozanimod (RPC1063) is an immunomodulator that has been recently approved by the FDA (2020) for the treatment of relapsing-remitting multiple sclerosis (RRMS). It is a selective agonist of the sphingosine-1-phophate receptors 1 and 5, expressed on naïve and central memory T and B cells, as well as natural killer (NK) cells, and is involved in lymphocyte trafficking. Oral administration of ozanimod was reported to result in rapid and reversible reduction in circulating lymphocytes in multiple sclerosis (MS) patients, however, only minimal effect on NK cells was observed. In this study, we sought to investigate the effect of ozanimod on NK cells and assess whether they play any role in ozanimod-induced remission in experimental autoimmune encephalomyelitis (EAE), the animal model of MS. Methods: Active EAE induction was done in C57BL/6 female mice, followed by daily oral treatment with ozanimod (0.6mg/kg) starting at disease onset (score 1). Flow cytometry of blood and CNS was performed 24 hours after the last oral dose of ozanimod treatment in diseased mice. Histological analysis of lumbar spinal cord was performed for evaluating the level of inflammation and demyelination. Depletion of peripheral NK cells was done using anti-NK1.1 mouse antibody (mAb) at day 5 post-EAE induction. Results: Ozanimod was effective in reducing the clinical severity of EAE and reducing the percentage of autoreactive CD4+ and CD8+ T cells along with significant inhibition of lymphocyte infiltration into the spinal cord, accompanied by reversed demyelination. Furthermore, ozanimod treatment resulted in a significant increase in the frequency of total NK cells in the blood and CNS along with upregulation of the activating receptor NKG2D on CD27low/- NK cell subset in the CNS. The effectiveness of ozanimod treatment in inhibiting the progression of the disease was reduced when NK cells were depleted using anti-NK1.1 mAb. Conclusion: The current study demonstrated that ozanimod treatment significantly improved clinical symptoms in EAE mice. Ozanimod and anti-NK1.1 mAb appear to function in opposition to one another. Collectively, our data suggest that ozanimod-mediated remission is associated with increased percentages of total NK cells and CD27low/- NK cells expressing the activating receptor, NKG2D in the CNS.